1984
DOI: 10.1073/pnas.81.4.1135
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell proteinase visualization and quantification using a fluorescent transition-state analog probe.

Abstract: The fluorescent proteinase transition-state analog inhibitor, dansyl-L-argininal (DnsArgH), may be a selective probe of cysteine and serine-type proteinases in a fibrosarcoma tumor cell line (HSDM1C1). DnsArgH binds with high affinity to proteinases because of its transition-state analog properties, and on association it gives a dramatically increased fluorescent yield. The DnsArgH binding is inhibited by the serine proteinase inhibitor diisopropyl fluorophosphate and by the cysteine proteinase inhibitor p-chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…An amino group (8) in analogy to ACoA, which served as template for the inhibitor design, 16 led to an inactive compound. This was also true for substituents with electron-withdrawing properties similar to the nitro group, as trifluoromethyl (14), nitril (15) and halogens (21,22). Furthermore, no activity was observed for molecules bearing potential hydrogen bond acceptors like 7, 10, the carboxylate 11, 24 and 25.…”
Section: Essentiality Of the Nitro-group And Ames Testmentioning
confidence: 99%
See 1 more Smart Citation
“…An amino group (8) in analogy to ACoA, which served as template for the inhibitor design, 16 led to an inactive compound. This was also true for substituents with electron-withdrawing properties similar to the nitro group, as trifluoromethyl (14), nitril (15) and halogens (21,22). Furthermore, no activity was observed for molecules bearing potential hydrogen bond acceptors like 7, 10, the carboxylate 11, 24 and 25.…”
Section: Essentiality Of the Nitro-group And Ames Testmentioning
confidence: 99%
“…The gathered information enabled us to design fluorescent inhibitors, which may be useful tools to investigate enzyme inhibitor interactions and to visualize the target in cells. 21,22 Finally, selected compounds were examined regarding their potency to inhibit signal molecule production in P. aeruginosa PA14 cells. Thereby, we additionally applied a novel strategy to reduce costs and time by the usage of a pqsH-deficient mutant which has been selected from a transposon mutant library.…”
Section: And 5)mentioning
confidence: 99%
“…The current investigation demonstrates that HSDMICl cells can be experimentally proliferated as multicellular tumor spheroids on an agar surface. We chose to evaluate this particular cell line based upon its known bone-resorbing activity (Goldhaber, 1960), and its phenotypic characterization regarding the secretion of prostaglandin Ez throughout the cell cycle Tashjian et al, 1972), as well as the presence of serine and cysteine proteinases associated with its cell membrane (Kozlowski et al, 1984;Wezeman et al, 1983). We chose to study the relationship of PGE2 to bone cell viability, proliferation, and bone resorption, since this prostaglandin is the principal product of secretion of the HSDMlCl cells and its presence in cultures mimics the presence of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanisms may depend, in part, upon cell proteinase secretion. We have recently demonstrated that HSDMlCl tumor cells have a cell membrane concentration of diisopropyl fluorophosphate and p-chloromercuribenzoate-inhibitable serine and cysteine proteinases, as demonstrated by the binding of a fluorescent transition-state analog probe (dansyl-L-argininal, DAL) to enzyme active sites (Kozlowski et al, 1984;Wezeman et al, 1983). It is widely expressed that the invasive characteristic of certain tumor cell types is that of proteinase secretion (Strauli et al, 1980), and a wide variety of proteinases have been shown to be involved in the degradation of bone extracellular matrix (Strauli et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation